Potential roles of PIWI-interacting RNAs in lung cancer - Jian, Zheng; Han, Yichao; Li, Hecheng (Frontiers in Oncology, 2022)
Lung cancer is a malignant tumor with high morbidity and mortality in the world today. Emerging evidence suggests that PIWI-interacting RNAs (piRNAs) are aberrantly expressed in a variety of human cancers, including lung cancer. Despite the poorly understood mechanism, piRNAs may work as carcinogenic roles or tumor suppressors by engaging in a variety of cancer-associated signaling pathways. Therefore, they might be able to serve as potential diagnostic or prognostic indicators, as well as therapeutic targets in lung cancer. This review will discuss the new findings of piRNAs, including their biosynthetic processes, mechanisms of gene expression suppression, as well as how these intriguing transcripts have been examined in lung cancer samples to determine their involvement in cancer progression.